2018
DOI: 10.1073/pnas.1720448115
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of ultrafast large-scale dynamics of an enzyme under turnover conditions

Abstract: SignificanceThe potential effect of conformational dynamics of enzymes on their chemical steps has been intensely debated recently. We use single-molecule FRET experiments on adenylate kinase (AK) to shed new light on this question. AK closes its domains to bring its two substrate close together for reaction. We show that domain closure takes only microseconds to complete, which is two orders of magnitude faster than the chemical reaction. Nevertheless, active-site mutants that reduce the rate of domain closur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
147
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 38 publications
17
147
0
Order By: Relevance
“…The stabilization may also result in lower interconversion rate between open and closed states in stable mutants. This is in agreement with recent single-molecule FRET study in Adk where mutations that reduced the rate of interconversion also reduced the k cat (41).…”
Section: Discussionsupporting
confidence: 93%
“…The stabilization may also result in lower interconversion rate between open and closed states in stable mutants. This is in agreement with recent single-molecule FRET study in Adk where mutations that reduced the rate of interconversion also reduced the k cat (41).…”
Section: Discussionsupporting
confidence: 93%
“…Aside from accelerating certain biochemical reactions, enzymes also inhibit undesired, off-pathway reactions involving highly reactive intermediate species (2). The collective dynamics of enzyme and substrate are often tightly coupled to the catalytic cycle (3)(4)(5)(6). For example, substrate binding can shift the enzyme's conformational distribution to structurally and electrostatically re-organize the active site.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to D152, however, this shift leads to a proportional reduction of the enzymatic activity, suggesting that the effect of V164R is more directly linked to the minoration of the dynamics of the open:close cycle. [33]. They propose that numerous cycles of conformational rearrangements, occurring on time scales 100-200 times faster than the turnover rate, are required to find the optimal orientation of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst our results agree with Kovermann et al [32] who found that an arrested closed conformation reduced catalytic activity, we can't fully conclude that there is a causal relationship. Aviram et al [33] have shown that there is a relationship between the domain opening and closing times that can measurably modulate enzymatic activity, however, this doesn't extend to the open and closed equilibrium.…”
Section: Computational Arginine Scan Identifies Distinct Mutations Anmentioning
confidence: 99%